Optical and electrochemical detection of a verotoxigenic E. coli gene using DNAzyme-labeled stem-loops - Longinotti, G. (2017)
Fil: Longinotti, G. Instituto Nacional de Tecnología Industrial. INTI-Procesos Superficiales; Argentina